2014
DOI: 10.4238/2014.june.9.17
|View full text |Cite
|
Sign up to set email alerts
|

Drynaria total flavonoids decrease cathepsin K expression in ovariectomized rats

Abstract: ABSTRACT. This study investigated the effects of Drynaria total flavonoids on cathepsin K serum concentrations and gene expression, biomechanics and bone mineral density (BMD) of the tibial shaft in ovariectomized rat models of osteoporosis, and mechanism in the prevention and cure of osteoporosis. Seventy-two female SpragueDawley rats were divided into six groups. The rats in each group were subjected to gastric lavage after the model was established. The tibial shaft of the right hindlimb was obtained to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Palacios et al demonstrated that estrogen directly binds with ER α , a membrane receptor expressed on osteoclast precursors, and decreases the formation of TRAP-expressing osteoclasts [ 27 ]. Cathepsin K plays critical roles in osteoclast bone resorption; Shi et al reported that cathepsin K was increased in an animal model of postmenopausal osteoporosis [ 28 ]. In our study, we determined that RANK, TRAP, and cathepsin K were downregulated in an obvious manner in the osteoclast pathway via WikiPathways database matching.…”
Section: Discussionmentioning
confidence: 99%
“…Palacios et al demonstrated that estrogen directly binds with ER α , a membrane receptor expressed on osteoclast precursors, and decreases the formation of TRAP-expressing osteoclasts [ 27 ]. Cathepsin K plays critical roles in osteoclast bone resorption; Shi et al reported that cathepsin K was increased in an animal model of postmenopausal osteoporosis [ 28 ]. In our study, we determined that RANK, TRAP, and cathepsin K were downregulated in an obvious manner in the osteoclast pathway via WikiPathways database matching.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of POP, the pathogenesis based on the theory of traditional Chinese medicine is mainly derived from the idea of "the kidneys promote bone growth" and "if the qi and blood are not clear, it is painful", and the treatment rules are mainly based on nurturing the kidney and improving the sperm, activating the blood and improving the gas and dissolving the stasis. Bone fragments in traditional medicine to supplement flavonoids [24][25][26] , icariin [27][28][29][30][31][32], and artificial tiger bone meal are active ingredients in the treatment of POP and may clinically improve osteoporosis symptoms with the approval of the CFDA (State Food and Drug Administration).…”
Section: Discussionmentioning
confidence: 99%
“…Ang et al [18] found that naringin can inhibit the formation and bone resorption of OC (Osteoclast, OC), which is realized by inhibiting the expression of RANK, activating nuclear factor κB(NF-κB) and phosphorylating ERK. Shi Xiaolin et al [19] observed and studied the effects of total flavonoids from bone clavicle on CTSK serum concentration and left tibial metaphysis gene expression in ovariectomized rat model of osteoporosis. It was found that serum cathepsin K in ovariectomized rat model treated by total flavonoids from bone clavicle was inhibited, and the mRNA expression of cathepsin K in left tibial metaphysis was also decreased as its concentration decreased.…”
Section: Rhizoma Drynariaedmentioning
confidence: 99%